Implementation of Hypertension Exercise in Elderly with Hypertension in Cinta Rakyat Village Deli Serdang Regency - Dior Manta Tambunan; Jhon Roby Purba; Popy Aldiana; Asril Jon Briko Tanjung; Berkah Ridho Nainggolan; Frans Sesep Manogitua Marbun; Agnes Oktavia Br. Ginting; Aprina Sabine Sakerebau; Bertua Mitra Debora; Cahaya Nurtioma Purba; Chalida Annisa; Desi Fransisca Siahaan; Bella Roria Pardede (Universitas Malahayati Lampung, 2023)
ABSTRACT Elderly is someone who is aged 60 years or more. Many problems are often found in the elderly, one of them is hypertension. Hypertension is a serious medical condition that can increase the risk of heart, brain, kidney, and other diseases. Hypertension is the main cause of premature death worldwide, most (two-thirds) live in low-and-middle-income countries. Various efforts can be made to control blood pressure, including hypertension exercise. Hypertension exercise is believed to be able to control blood pressure because when carrying out exercise movements, blood vessels will dilate and relax so that blood pressure decreases. This community service aimed to improve the community's healthy lifestyle in controlling hypertension by implementing Hypertension exercise. This activity was carried out on the elderly with 22 respondents. Before the implementation of this activity, the first was carried out by filling in demographic data, drugs consumed, and routine control history every month as well as measuring vital signs before and after the implementation of the Hypertension exercise. The findings show that the majority of respondents who participated in the implementation of this Hypertension Exercise were >70 years old (45.5%); Female (59.1%); not taking hypertension medication (54.5%); not routine control (86.4%); and classification of hypertension majority degree 1 (31.8%). The average value of blood pressure before the implementation of the Hypertension Exercise was 2.95 and decreased significantly after the implementation of the Hypertension Exercise to 2.32. It can be concluded that there was a significant decrease in blood pressure after the implementation of hypertension exercises, the pre-test average value was 2.95 and the post-test was 2.32. It is recommended that village officials and Public Health Care officers conducted a Hypertension Exercise program as an implementation discourse in improving the quality of life of the Elderly with Hypertension. The implementation can be carried out in Cinta Rakyat Village, Deli Serdang Regency, regularly 2-3 times a week. Keywords: Elderly, Hypertension, Hypertension Exercise